Immigration and settlement of Transnational Marriage between Chinese Men and Thai Women in Phuket : The Case Study of Ethnic Issue in Post Modern Society - Pheempimol Chatsuwannakit (Prince of Songkla University, 2021)
Thesis (M.A., Chinese Studies)--Prince of Songkla University, 2018